KARAKTER KEPEMIMPINAN DEMOKRATIS DENGAN KONSEP-KONSEP ISLAM DILEMBAGA PENDIDIKAN, BESERTA PELUANG DAN TANTANGANNYA - Ega Rismasita; Parasih; Muhammad Sirozi (LP2M IAIN Sultan Amai Gorontalo, 2025)
Democratic leadership in Islamic educational institutions is a crucial concept rooted in Islamic principles of deliberation, justice, and trustworthiness, aiming to foster inclusive, participatory environments and develop critical, responsible individuals. This study aims to analyze the foundational concepts, implementation mechanisms, opportunities, and challenges of Islamic-based democratic leadership in educational institutions. The research employs a qualitative descriptive method using a literature review approach, analyzing data from relevant academic sources. Findings indicate that democratic leadership is implemented through the active involvement of teachers and staff in deliberation processes, granting freedom of opinion, and upholding justice, which subsequently enhances teacher professionalism and establishes a healthy, harmonious organizational culture. Nevertheless, key challenges persist, including dominant authoritarian cultural aspects, rigid policies, and limitations in funding for staff training and necessary facilities. Comprehensive and sustainable strategies are essential to optimize these democratic Islamic values to achieve high-quality and competitive Islamic education. Keywords: Democratic Leadership, Islamic Education, Deliberation, Challenges.